Wideband circular patch antenna with Ishaped structure for horizontal omnidirectional gain enhancement - Liu, Ankang (2021)
A wideband circular patch antenna with enhanced omnidirectional gains in the horizontal plane is presented. The gain enhancement over 1 GHz bandwidth is achieved by loading a low-profile 'I-shaped' structure (ISS) without increasing antenna's thickness. The effective refractive index of the ISS is larger, over a wide bandwidth than that of the conventional substrate with the same material. Therefore, the artificial structure behaves as a lens to refract the electromagnetic wave which is parallelly incident to the ISS and thus is able to concentrate the energy and enhance the antenna's horizontal radiation performance. In addition, the proposed antenna achieves a relative bandwidth of 19% through combining the resonant frequency for the TM₀₁ mode and another resonant frequency excited by the coupling between the circular patch and the unit cells for verifying the wideband gain enhancement of the ISS. Both simulation and measurement results indicate that the proposed antenna achieves 0.5-2.0 dB gain increment within the operating bandwidth compared with the unloaded antenna on the same ground.